2015
DOI: 10.1128/aac.04306-14
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated Handwashing Sinks as the Source of a Clonal Outbreak of KPC-2-Producing Klebsiella oxytoca on a Hematology Ward

Abstract: We investigated sinks as possible sources of a prolonged Klebsiella pneumonia carbapenemase (KPC)-producing Klebsiella oxytoca outbreak. Seven carbapenem-resistant K. oxytoca isolates were identified in sink drains in 4 patient rooms and in the medication room. Investigations for resistance genes and genetic relatedness of patient and environmental isolates revealed that all the isolates harbored the bla KPC-2 and bla TEM-1 genes and were genetically indistinguishable. We describe here a clonal outbreak caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
86
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 15 publications
2
86
0
1
Order By: Relevance
“…Data from different dispersal experiments suggest that although P-traps can act as the source or the reservoir of pathogens, the physical presence of the organism in the sink bowl or colonization of the strainer is necessary for the dispersal to occur. Colonization of strainers or drains reported in earlier studies (7,10,13,24,37) was perhaps a result of ascending biofilm growth from the P-trap to the strainer or introduction through contaminated fluids. Many of the studies used swab samples, which likely sampled the strainer rather than P-trap water (17,20).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data from different dispersal experiments suggest that although P-traps can act as the source or the reservoir of pathogens, the physical presence of the organism in the sink bowl or colonization of the strainer is necessary for the dispersal to occur. Colonization of strainers or drains reported in earlier studies (7,10,13,24,37) was perhaps a result of ascending biofilm growth from the P-trap to the strainer or introduction through contaminated fluids. Many of the studies used swab samples, which likely sampled the strainer rather than P-trap water (17,20).…”
Section: Discussionmentioning
confidence: 91%
“…D espite early reports (1)(2)(3)(4)(5), the premise that hand-wash sink traps can act as reservoirs of bacteria that cause nosocomial infections has been frequently overlooked. There has recently been an alarming increase in sink-related outbreaks worldwide, with many reports establishing an observational link (6)(7)(8)(9)(10)(11)(12)(13). A sink often operates as an open conduit to wastewater in a patient care area that is often in the same room as the patient.…”
mentioning
confidence: 99%
“…On the other hand, our previous study showed that CRE (Enterobacter and Klebsiella species) survived poorly in a hospital environment for 24 h and was infrequently isolated from environmental surfaces in rooms housing CRE-colonized/ infected patients (27); thus, the role of hospital environmental surfaces for CRE transmission is yet to be clarified. Some authors have described environmental reservoirs of CPE related to transmission in health care settings (28), including sinks (29,30), soap dispensers (24), and hospital wastewater systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Since characterization, K. michiganensis has been reported in clinical settings, including as a cause of diarrhea in a hematopoietic stem cell transplant recipient (3), from a sample of fluid from an abdominal fistula (4), in an investigation of hospital-acquired colonization by a New Delhi metallo-βlactamase-producing organism (5) and as an invasive, Klebsiella pneumoniae carbapenemase (KPC)-producing pathogen causing bloodstream infection (6). While the role of K. oxytoca in nosocomial outbreaks is established (7)(8)(9)(10)(11), there have been no reported outbreaks involving K. michiganensis to date. Similar to K. oxytoca, K. michiganensis carries a chromosomally-encoded OXY-type (Ambler class A) β-lactamase (12,13) (also labelled as K1 in K. oxytoca (14)) which mediates resistance to amino-and carboxy-penicillins (e.g.…”
Section: Introductionmentioning
confidence: 99%